Partially distributed outer approximation - Alexander Murray; Timm Faulwasser; Veit Hagenmeyer; Mario E. Villanueva; Boris Houska (Journal of Global Optimization, 2021)
This paper presents a novel partially distributed outer approximation algorithm, named PaDOA, for solving a class of structured mixed integer convex programming problems to global optimality. The proposed scheme uses an iterative outer approximation method for coupled mixed integer optimization problems with separable convex objective functions, affine coupling constraints, and compact domain. PaDOA proceeds by alternating between solving large-scale structured mixed-integer linear programming problems and partially decoupled mixed-integer nonlinear programming subproblems that comprise much fewer integer variables. We establish conditions under which PaDOA converges to global minimizers after a finite number of iterations and verify these properties with an application to thermostatically controlled loads and to mixed-integer regression.
Keywords: 510; Mixed integer programming; Distributed optimization; Outer approximation; Global optimization